2021
DOI: 10.3389/fmed.2021.779272
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Characteristics of Patients With Anti-MDA5–Antibody-Positive Dermatomyositis in 18F-FDG PET/CT: A Pilot Study

Abstract: Objective: To elucidate the 18F-fluorodeoxyglucose (FDG) PET/CT characteristics and its prognostic value in the patients with anti-melanoma differentiation associated protein 5 antibody positive (anti-MDA5+) dermatomyositis (DM).Methods: This retrospective cross-sectional study included 26 patients with anti-MDA5+ DM and 43 patients with anti-MDA5 negative (anti-MDA5–) idiopathic inflammatory myopathy (IIM) who were examined by 18F-FDG PET/CT from January 1, 2017 to December 31, 2020. The maximum standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Between February 2018 and April 2020, our hospital treated 80 DM patients, categorizing them into MDA5 positive (20 patients) and MDA5 negative (60 patients) groups, with all participants consenting to the study approved by the Hospital Ethics Committee. The diagnosis of DM still relies on the criteria set by Bohan and Peter in 1975, which encompass typical symmetrical muscle weakness near the body, raised muscle enzyme levels, electromyography (EMG) signs of muscle damage, unusual muscle biopsy findings, and distinctive rashes such as Gottron's sign and periungual erythema 19 . A diagnosis of DM is confirmed if a patient exhibits the listed five symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Between February 2018 and April 2020, our hospital treated 80 DM patients, categorizing them into MDA5 positive (20 patients) and MDA5 negative (60 patients) groups, with all participants consenting to the study approved by the Hospital Ethics Committee. The diagnosis of DM still relies on the criteria set by Bohan and Peter in 1975, which encompass typical symmetrical muscle weakness near the body, raised muscle enzyme levels, electromyography (EMG) signs of muscle damage, unusual muscle biopsy findings, and distinctive rashes such as Gottron's sign and periungual erythema 19 . A diagnosis of DM is confirmed if a patient exhibits the listed five symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The database search identified 252 records found and 236 records were excluded after title/abstract screening and full-text content because those did not provide any relevant information on the topic of this review (Figure 1). Sixteen articles were eligible for a more detailed description in this review (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Literature Search Study and Patient Characteristicsmentioning
confidence: 99%
“…Two studies (26,29) demonstrated a good concordance between [ 18 F]FDG-PET/CT and HRCT to detect ILD while 1 study (17) showed that HRCT better identified ILD patients (18/24 vs. 7/24). Three studies (21,29,30)…”
Section: [ 18 F]fdg-pet/ct and Cancer Diagnosismentioning
confidence: 99%
“…Our previous study also indicated that higher 18 F-FDG uptake by the interstitial lesions observed in the PET/CT images of IIM patients was significantly associated with RP-ILD and unfavorable outcome. [59,62] Moreover, it seems reductive and inefficient to use a single clinical factor to predict RP-ILD in heterogeneous diseases. A holistic approach should be used to provide a better predictive model for RP-ILD based on multiple clinical, immunological, and radiographic factors.…”
Section: Journal Of Translational Internal Medicine / Aopmentioning
confidence: 99%
“…Predictive factor First author Demographic Age ≥ 57 years at disease onset Li et al [10] IIM subtypes CADM Liang et al [4] Gan et al [38] Wong et al [56] Clinical manifestations or complications Fever Li et al [57] Periungual erythema Li et al [10] Li et al [57] Lower OI Gui et al [58] MYOACT Li et al [57] History of TB Wong et al [56] On-admission laboratory findings Serum ferritin levels Motegi et al [5] Elevated CRP levels Li et al [57] MAAs or MSAs Anti-MDA5 antibody Nombel et al [28] Chen et al [45] Biomarkers Median sCD163 levels Enomoto et al [51] Median sCD206 levels Shen et al [52] Serum Gal-9 levels Peng et al [60] Serum YKL-40 levels Jiang et al [12] Serum CYFRA21-1 levels Gui et al [58] Serum neopterin levels Liang et al [61] Pulmonary function tests DL CO % Liang et al [4] Liang et al [59] Imaging Lower zone consolidation in HRCT Gui et al [58] Bilateral lung SUV mean Liang et al [59] Bilateral lung SUV max Cao et al [62] Mediastinal lymph node SUV mean Liang et al [59] Integrated data model DLM model Liang et al [59] RRP model Li et al [57] IIM: idiopathic inflammatory myopathy; CADM: clinical amyopathic dermatomyositis; OI: oxygen index; MYOACT: myositis disease activity assessment visual analogue scales; TB: tuberculosis; CRP: C-reactive protein; MAAs: myositis-associated autoantibodies; MSAs: myositis-specific autoantibodies; MDA5: melanoma differentiation-associated gene 5; sCD163: soluble CD163; sCD206: soluble CD206; Gal-9: galectin-9; YKL-40: chtinase-3-like-1 protein; CYFRA21-1: cytokeratin-19 fragment; DL CO %: percent-predicted diffusing capacity of the lung for carbon monoxide; HRCT: high-resolution computed tomography; SUV: standardized uptake value; DLM model: a multiparametric score contained DL CO %, lung and mediastinum; RRP model: a multiparametric model including fever, periungual erythema, elevated CRP level, and presence of anti-MDA5 antibody and anti-Ro-52 antibody.…”
Section: Itemsmentioning
confidence: 99%